Comparative assessment of on-farm greenhouse gases emission from male-headed and female-headed rice farms in Babol county (Mazandaran province, Iran) - Hadi Veisi; Anahita Valiollahi; Abdol Majid Mahdavi Damghani; Surror Khoramdel (علوم محیطی)
Introduction: Since the emission of greenhouse gases (GHGs) has changed the chemical composition of the atmosphere, a wide global consensus has emerged on the anthropogenic accumulation of GHGs in the atmosphere. Women have a vital role in agriculture, but the gap in gender-based studies on the significant effects of agriculture on carbon emissions through production has not yet been filled. Therefore, a detailed analysis of how the gender factor affects GHGs emission is essential. In this sense, the present study investigated the effect of farmers' gender on global warming potential (GWP) in rice production systems during 2014-2015 in Babol County in Mazandaran Province, Iran. To this end, GHG emissions from male- and female-head rice farms were compared using the carbon input (kg.C.equivalent.ha−1) and output (kg.C.equivalent.ha−1), sustainability indices, and carbon efficiency. Material and methods: The data was gathered from 120 rice farmers (60 males and 60 females) through questionnaires and face-to-face interviews. The methodology of the Intergovernmental Panel on Climate Change was used to calculate the GHGs emission of each farm. Each GHG such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) has GWP, which is the warming influence relative to that of carbon dioxide. Emissions were measured in terms of a reference gas, CO2 and reported based on CO2 equivalent. The method was restricted to a farm boundary and extracted into spreadsheets, which compute the baseline CH4 and N2O emissions for each farm. The indices of sustainability were estimated by assessing the temporary changes in output/input or (output-input)/input ratios of C to determine the share of anthropogenic GHGs emission in the atmosphere to determine the intensity of energy flow, carbon savings, and GHG emissions from women-headed and men-headed rice farms. Results and discussion: The results demonstrated considerable differences between farms headed by women and headed by men in terms of GWP (2930.31 and 3291.35 kg.CO2.equivalent.ha-1 for female-headed and male-headed farms, respectively) since more agricultural inputs were employed in farms headed by men. The dominant share of GWP for farms headed by men and women from the highest to the lowest was due to fossil fuels, machinery, and N fertilizers. The indices of carbon efficiency and carbon sustainability were respectively 3.88 and 2.88 in farms headed by women, and 3.55 and 2.55 in farms headed by men. Conclusion: The largest proportion of GHGs emission was due to fossil fuels in both female-headed and male-headed farms. This was attributed to outdated diesel pumps, excessive machinery traffic in agroecosystems, incompatibility between the power and performance of the equipment with the requirements of female-headed farms, and the relatively low price of fossil fuels. In line with these results, it can be concluded that resource-use patterns for the establishment, production, harvesting, and transportation in the rice fields are compatible with landscapes and masculine norms. Females, like males, used machinery and tools that consumed large amounts of fossil fuels; however, female-headed farms were smaller and wasted more energy, which in turn increased the level of mitigation. The findings suggested that farms by women produced fewer GHGs because the carbon input was used in a more environment-friendly manner than in the male-headed farms. Finally, several “soft” policies, such as gender-sensitive capacity development programs, are proposed to address the share of farmers in the emission of GHGs from subsistence farming systems on a gender basis.